Examining Trust in Social Network Sites - Beisembayev, Olzhas (2010)
The creation of Web 2.0 has opened up new ways to communicate between individuals. Social Media significantly different from traditional media has brought revolutionary changes in the way marketers today promote brands, products and services. This study explores role and significance of Social Media as new promotion tool. It also explores place of social network sites in contemporary world of communication. Research has been done to explore most important issues that exist today in social network sites. Based on the literature reviewed, hypotheses have been formed to examine the factors that affect trust in social network sites. A questionnaire has been designed and administered among SNS users. A total of 87 respondents were participated in the web based survey. Statistical software SPSS 16.0 was used to run series of analyses of the data set. Findings of statistical results indicated SNS users’ profiles, patterns and frequency of usage, privacy and security concerns, trust and intentions of SNS users online.